Device-Associated Infection Rates in 20 Cities of India, Data Summary for 2004–2013: Findings of the International Nosocomial Infection Control Consortium. (26th November 2015) - Mehta, Yatin; Jaggi, Namita; Rosenthal, Victor Daniel; Kavathekar, Maithili; Sakle, Asmita; Munshi, Nita; Chakravarthy, Murali; Todi, Subhash Kumar; Saini, Narinder; Rodrigues, Camilla; Varma, Karthikeya; Dubey, Rekha; et al.
Abstract : OBJECTIVE: To report the International Nosocomial Infection Control Consortium surveillance data from 40 hospitals (20 cities) in India 2004–2013. METHODS: Surveillance using US National Healthcare Safety Network's criteria and definitions, and International Nosocomial Infection Control Consortium methodology. RESULTS: We collected data from 236, 700 ICU patients for 970, 713 bed-days Pooled device-associated healthcare-associated infection rates for adult and pediatric ICUs were 5.1 central line–associated bloodstream infections (CLABSIs)/1, 000 central line–days, 9.4 cases of ventilator-associated pneumonia (VAPs)/1, 000 mechanical ventilator–days, and 2.1 catheter-associated urinary tract infections/1, 000 urinary catheter–days In neonatal ICUs (NICUs) pooled rates were 36.2 CLABSIs/1, 000 central line–days and 1.9 VAPs/1, 000 mechanical ventilator–days Extra length of stay in adult and pediatric ICUs was 9.5 for CLABSI, 9.1 for VAP, and 10.0 for catheter-associated urinary tract infections. Extra length of stay in NICUs was 14.7 for CLABSI and 38.7 for VAP Crude extra mortality was 16.3% for CLABSI, 22.7% for VAP, and 6.6% for catheter-associated urinary tract infections in adult and pediatric ICUs, and 1.2% for CLABSI and 8.3% for VAP in NICUs Pooled device use ratios were 0.21 for mechanical ventilator, 0.39 for central line, and 0.53 for urinary catheter in adult and pediatric ICUs; and 0.07 for mechanical ventilator and 0.06 for central line in NICUs. CONCLUSIONS: Despite a lower device use ratio in our ICUs, our device-associated healthcare-associated infection rates are higher than National Healthcare Safety Network, but lower than International Nosocomial Infection Control Consortium Report. Infect. Control Hosp. Epidemiol. 2016;37(2):172–181